Negative radiation-sensitive resin composition and formation method of insulating film for organic el element
Patent Information
- Application Number
- KR1020220043012
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-07
- Filing Date
- 2022-04-06
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2042-04-06
Smart Images

Figure 112022036961092-PAT00004_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a negative-type radiation-sensitive resin composition, an insulating film for an organic EL device, a method for forming an insulating film for an organic EL device, and an organic EL device. Background Technology
[0002] As one of the light-emitting devices currently under development, an organic electroluminescence (EL) device having a stacked structure including an anode layer, an organic light-emitting layer, and a cathode layer is known. As a display device having an organic EL device, a touch panel-attached organic EL device having a touch panel formed on the front surface of the device is known (see Patent Document 1).
[0003] An organic EL device with a touch panel attached is manufactured, for example, by bonding a touch panel to a substrate on which an organic EL element is formed through an adhesive layer. The touch panel is typically manufactured by forming a touch panel member, such as a sensor electrode, on a support substrate for the touch panel.
[0004] Meanwhile, Patent Document 2 discloses a curable resin composition comprising a silsesquioxane having thiol groups and a compound having multiple allyl groups, and describes that said composition can be used to form a coating layer or an adhesive layer for liquid crystal panels, EL panels, etc. Additionally, Patent Document 3 discloses a photosensitive composition comprising a polysiloxane having thiol groups and a polyfunctional acrylate compound, and describes that the durability of the pattern film can be increased by forming a pattern film on a substrate using said composition. Prior art literature
[0005] Japanese Published Patent Application No. 2015-161806, Japanese Published Patent Application No. 2012-180464, Japanese Published Patent Application No. 2010-039056 The problem to be solved
[0006] As described above, when a touch panel is bonded to a substrate on which an organic EL element is formed through an adhesive layer, the overall thickness of the organic EL device with the touch panel attached increases. In the case of a device with a large thickness, it is prone to breakage or functional degradation when bent. Furthermore, thinning itself is desired for various display devices. Therefore, it is believed that by forming a touch panel directly on a substrate on which an organic EL element is formed using methods such as lithography or etching, the overall thickness of the display device, such as an organic EL device with a touch panel attached, can be reduced.
[0007] However, in conventional methods using materials containing polyfunctional (meth)acrylates, etc., as curable components, heating at a temperature exceeding 100°C, preferably exceeding 120°C, is required to cure the insulating film for forming a touch panel. When forming an insulating film on a substrate on which an organic EL element is formed, there is a problem that heating at a temperature exceeding 100°C, particularly exceeding 120°C, causes degradation of the organic light-emitting layer.
[0008] Meanwhile, when an insulating film is formed using conventional materials at a temperature of 120°C or lower, particularly 100°C or lower, the resulting insulating film tends to fail to withstand etching agents or oxygen ashing for wiring formation, making it difficult to manufacture a touch panel structure. There is a demand for the development of a radiation-reducing resin composition that can obtain an insulating film with sufficient etching agent resistance and oxygen ashing resistance even with relatively low-temperature heating, not limited to insulating films for organic EL devices attached to touch panels, but also for various other applications such as insulating films for display devices.
[0009] The present invention is made based on the above circumstances and aims to provide a negative-type radiation-reducing resin composition that can obtain a cured film having sufficient lithography performance and sufficient chemical resistance and oxygen ashing resistance even by heating at a relatively low temperature (e.g., 120°C or lower), an insulating film for an organic EL device and an organic EL device obtained using the negative-type radiation-reducing resin composition, and a method for forming an insulating film for an organic EL device using the negative-type radiation-reducing resin composition. means of solving the problem
[0010] The invention made to solve the above problem is a negative-type radiation-reducing resin composition described in [1] or [2] below.
[0011] [1] A negative-type radiation-reducing resin composition comprising (A) a polysiloxane having at least one thiol group, (B) a polyfunctional methacrylate, and (C) a photopolymerization initiator.
[0012] [2] A negative-type radiation-reducing resin composition comprising (A) a polysiloxane having at least one thiol group, (B) a polyfunctional methacrylate, and (C) a photopolymerization initiator, wherein the viscosity measured using an E-type viscometer under conditions of 25°C and 50 rpm is 0.5 mPa·s or more and 20 mPa·s or less.
[0013] Another invention made to solve the above problem is an insulating film for an organic EL device formed by the negative-type radiation-reducing resin composition described in [1] or [2] above.
[0014] Another invention made to solve the above problem is a method for forming an insulating film for an organic EL device, comprising: a process of forming a film by applying a negative-type radiation-sensitive resin composition described in [1] or [2] above directly or indirectly on a substrate; a process of irradiating at least a portion of the film with radiation after the process of forming the film; a process of developing the film after the process of irradiating the radiation; and a process of heating the film at a temperature of 60°C or higher and 120°C or lower after the process of developing.
[0015] Another invention made to solve the above problem is an organic EL device having an insulating film for the organic EL element described above. Effects of the invention
[0016] According to the present invention, a negative-type radiation-sensitive resin composition is provided, which can obtain a cured film having sufficient lithography performance and sufficient chemical resistance and oxygen ashing resistance even by heating at a relatively low temperature; an insulating film for an organic EL device and an organic EL device obtained using the negative-type radiation-sensitive resin composition; and a method for forming an insulating film for an organic EL device using the negative-type radiation-sensitive resin composition.
[0017] In addition, the curable resin composition described in Patent Document 2 contains a compound having multiple allyl groups, and since the allyl groups have low reactivity, only the en-thiol reaction proceeds. In contrast, the negative-type radiation-reducing resin composition of the present invention contains a polyfunctional methacrylate, so the en-thiol and conventional radical polymerization reactions by the methacrylate groups proceed simultaneously. Therefore, according to the present invention, a cured film with superior low-temperature curing properties and excellent solvent resistance is obtained.
[0018] In addition, the photosensitive composition described in Patent Document 3 contains polyfunctional acrylates, and while the acrylate groups have excellent reactivity, the viscosity of the composition increases and storage stability is poor because the en-thiol reaction proceeds even during storage of the composition. In contrast, the negative-type radiation-sensitive resin composition of the present invention contains polyfunctional methacrylates, so it can provide a composition with excellent storage stability. Brief explanation of the drawing
[0019] FIG. 1 is a cross-sectional view schematically showing an organic EL device according to one embodiment of the present invention. Specific details for implementing the invention
[0020] (Form for carrying out the invention)
[0021] <Negative-type radioactive resin composition>
[0022] A negative-type radiation-reducing resin composition according to one embodiment of the present invention comprises (A) a polysiloxane having at least one thiol group (hereinafter also referred to as "Component (A)"), (B) a polyfunctional methacrylate (hereinafter also referred to as "Component (B)"), and (C) a photopolymerization initiator (hereinafter also referred to as "Component (C)"), and preferably has a viscosity of 0.5 mPa·s or more and 20 mPa·s or less when measured using an E-type viscometer under conditions of 25°C and 50 rpm.
[0023] According to the present negative-type radiation-reducing resin composition, by containing components (A), (B), and (C), and preferably having a viscosity within the above range, a cured film having sufficient lithographic performance and sufficient chemical resistance and oxygen ashing resistance even with heating at a relatively low temperature can be obtained. Although the reason for this is not clear, it is inferred as follows. That is, it is inferred that in the present negative-type radiation-reducing resin composition, since the thiol group of the polysiloxane functions as an alkali-soluble group and a crosslinking group, the dissolution contrast of the obtained cured film is increased, and accordingly, excellent lithographic performance is exhibited. Furthermore, by forming a crosslinking structure through an en-thiol reaction between a polysiloxane having a siloxane structure and a multifunctional methacrylate having a methacrylate structure, a cured film having a structure in which a siloxane structure and a methacrylate structure coexist is obtained. For this reason, it is inferred that the resulting hardened film exhibits excellent stress relief, and accordingly, resistance to chemical solutions and oxygen ashing is exhibited. Below, each component of the negative-type radiation-reducing resin composition is described.
[0024] (A) Polysiloxane having at least one thiol group
[0025] The negative-type radiation-reducing resin composition comprises (A) a polysiloxane having at least one thiol group. In addition to component (A), the negative-type radiation-reducing resin composition comprises a compound ((B) a polyfunctional methacrylate) having two or more functional groups in one molecule capable of reacting with the thiol group, and an insulating film with excellent curability is formed by the reaction between component (A) and component (B). Furthermore, component (A) is a polysiloxane having siloxane bonds.
[0026] By including a polysiloxane having siloxane bonds in the negative-type radiation-reducing resin composition, the generation of outgassing during the manufacture of the insulating film can be suppressed, thereby enabling the production of an insulating film for organic EL devices with excellent porosity and transparency.
[0027] In addition, compounds having thiol groups can be photocured by an en-thiol reaction with compounds having carbon-carbon double bonds. Compared to radical polymerization systems commonly used in photocuring systems, the en-thiol reaction has advantages such as proceeding via UV irradiation regardless of the presence or absence of a polymerization initiator, not being inhibited by oxygen, and having small curing shrinkage.
[0028] (A) The component is a compound obtained by hydrolyzing and condensing a thiol group-containing alkoxysilane (a1) represented by the following formula (2) (hereinafter also referred to as “Component (a1)”).
[0029] R 1 Si(OR 2 )3(2)
[0030] Among the above formula (2), R 1 represents an aliphatic hydrocarbon group having 1 to 8 carbon atoms having at least one thiol group, or an aromatic hydrocarbon group having 6 to 8 carbon atoms having at least one thiol group, and R 2 It represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 8 carbon atoms, or an aromatic hydrocarbon group having 6 to 8 carbon atoms.
[0031] Aliphatic hydrocarbon groups having 1 to 8 carbon atoms may be in a straight chain or a branched chain. Examples include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, hexyl, heptyl, and octyl groups.
[0032] In the context of an aromatic hydrocarbon group having 6 to 8 carbon atoms, the term "aromatic hydrocarbon group" is a concept that includes not only groups consisting solely of a ring structure, but also groups in which a divalent aliphatic hydrocarbon group is additionally substituted into the ring structure, and it is sufficient if the structure contains at least an alicyclic hydrocarbon or an aromatic hydrocarbon. Examples include phenyl groups, benzyl groups, phenethyl groups, tolyl groups, and xylyl groups.
[0033] Among them, R 1 As such, from the perspective of low-temperature curability, an aliphatic hydrocarbon group having 1 to 6 carbon atoms having at least one thiol group is preferred, and also R 2 As for hydrolytic properties, an aliphatic hydrocarbon group having 1 to 3 carbon atoms is preferred.
[0034] Specific examples of the component (a1) represented by the above formula (2) include 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltripropoxysilane, 3-mercaptopropyltributhoxysilane, 1,4-dimercapto-2-(trimethoxysilyl)butane, 1,4-dimercapto-2-(triethoxysilyl)butane, 1,4-dimercapto-2-(tribupropoxysilyl)butane, 1,4-dimercapto-2-(tribupropoxysilyl)butane, 2-mercaptomethyl-3-mercaptopropyltrimethoxysilane, 2-mercaptomethyl-3-mercaptopropyltriethoxysilane, 2-mercaptomethyl-3-mercaptopropyltributhoxysilane, Examples include 2-mercaptomethyl-3-mercaptopropyltributoxysilane, 1,2-dimercaptoethyltrimethoxysilane, 1,2-dimercaptoethyltriethoxysilane, 1,2-dimercaptoethyltripropoxysilane, 1,2-dimercaptoethyltributoxysilane, etc., and any of the above example compounds may be used alone or in appropriate combination. Among the above example compounds, 3-mercaptopropyltrimethoxysilane is particularly preferred because it has high reactivity in hydrolysis reactions and is also easy to obtain.
[0035] In addition, in addition to component (a1), alkyltrialkoxysilanes (a2) (hereinafter also referred to as “component (a2)”) such as methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, phenyltrimethoxysilane, and phenyltriethoxysilane may be used. Component (a2) may be used alone or in combination of two or more types. By using these, the content of thiol groups can be adjusted, and thus the refractive index of the insulating film obtained at the end can be adjusted.
[0036] When component (a1) and component (a2) are used together, it is preferable that [moles of component (a2)] / [total moles of component (a1) and component (a2)] (molar ratio) be 0.7 or less, and more preferable that it be 0.5 or less. If the above molar ratio exceeds 0.7, the number of thiol groups included in the obtained component (A) decreases, so there is a risk that the curability of the insulating film will decrease, and the improvement effect on physical properties such as the hardness of the insulating film will also be insufficient. On the other hand, the above molar ratio may be 0, but it may be appropriately set to greater than 0.
[0037] (A) Component can be obtained by using component (a1) alone or in combination with component (a2), hydrolyzing them, and then condensing them. Through the hydrolysis reaction, the alkoxy groups contained in component (a1) or component (a2) become silanol groups, and alcohol is produced as a byproduct. The amount of water required for the hydrolysis reaction is preferably such that, for example, [moles of water used for the hydrolysis reaction] / [total moles of each alkoxy group contained in component (a1) and component (a2)] (molar ratio) is 0.4 or more and 10 or less. If the above molar ratio is 0.4 or more and less than 0.5, some alkoxy groups remain in the obtained component (A), but adhesion to inorganic materials is improved. Furthermore, if the above molar ratio is 0.5 or more and 10 or less, since substantially no alkoxy groups remain in the obtained component (A), it is easy to produce a thick film cured product. Meanwhile, if the above molar ratio does not satisfy 0.4, the alkoxy groups remaining without hydrolysis in component (A) become excessively numerous, which leads to a large amount of volatile components being generated during curing, making it difficult to produce a thick film cured product, and thus is undesirable. In addition, if the above molar ratio exceeds 10, the amount of water that must be removed during the subsequent condensation reaction (dehydration reaction) increases, which is economically disadvantageous.
[0038] As a catalyst used in the hydrolysis reaction, an acidic catalyst capable of functioning as a conventionally known hydrolysis catalyst may be optionally used. However, since it is necessary to substantially remove the acidic catalyst after the hydrolysis reaction, it is desirable that it be easy to remove. As such, formic acid is preferred because it has high catalytic activity and a low boiling point, and can be removed by reduced pressure. Examples of the above catalyst include components (a1), components (a2), their hydrolysates, solvents used during hydrolysis, and solid acid catalysts insoluble in water, which can be easily removed by methods such as filtration. Examples of solid acidic catalysts include cation exchange resins, activated clay, and carbon-based solid acids. Among these, cation exchange resins are preferred because they have high catalytic activity and are easy to obtain. As cation exchange resins, strong acid-type cation exchange resins and weak acid-type cation exchange resins may be used. Examples of strong acid type ion exchange resins include the Diaion SK series, the UBK series, the PK series, the HPK25 and PCP series (all product names manufactured by Mitsubishi Chemical Corporation), Amberlite IR120B, IR124, 200CT, 252, Amberjet 1020, 1024, 1060, 1220, Amberlite 15DRY, 15JWET, 16WET, 31WET, and 35WET (all product names manufactured by Organo Corporation). Examples of weak acid type ion exchange resins include the Diaion WK series, WK40 (all product names manufactured by Mitsubishi Chemical Corporation), Amberlite FPC3500, and IRC76 (all product names manufactured by Organo Corporation). The type of ion exchange resin used can be arbitrarily selected based on the reaction rate or suppression of side reactions, but a strongly acidic ion exchange resin is particularly preferred due to its reactivity.
[0039] The amount of acidic catalyst added is preferably 0.1 parts by mass or more and 25 parts by mass or less, with respect to 100 parts by mass of the total of component (a1) and component (a2), and more preferably 1 part by mass or more and 10 parts by mass or less. If the amount added exceeds 25 parts by mass, it tends to be difficult to remove in a subsequent process or to become economically disadvantageous. On the other hand, if the amount added does not satisfy 0.1 parts by mass, there is a tendency for the reaction not to proceed substantially or for the reaction time to be prolonged.
[0040] The reaction temperature and reaction time can be arbitrarily set depending on the reactivity of component (a1) or component (a2). The reaction temperature is typically 0°C or higher and 100°C or lower, and preferably 20°C or higher and 60°C or lower. The reaction time is 1 minute or higher and 2 hours or lower. The above hydrolysis reaction can be carried out in the presence or absence of a solvent, but it is preferable not to use a solvent. If a solvent is used, the type of solvent is not particularly limited, and one or more types of any solvent may be selected and used, but it is preferable to use the same solvent as that used in the condensation reaction described later.
[0041] After the hydrolysis reaction is completed, condensation is performed using an acidic catalyst or a basic catalyst. For the condensation reaction, a conventionally known dehydration condensation catalyst may be optionally used. When using an acid catalyst, formic acid is preferred because it has high catalytic activity and can be used in conjunction with the catalyst for the hydrolysis reaction. The reaction temperature and reaction time can be arbitrarily set according to the reactivity of component (a1) or component (a2), respectively. The reaction temperature is typically 40°C or higher and 150°C or lower, and preferably 60°C or higher and 100°C or lower. The reaction time is 30 minutes or more and 12 hours or less.
[0042] When using a basic catalyst, it is necessary to remove the acidic catalyst from the system after the hydrolysis reaction is completed; therefore, it is removed by methods such as reduced pressure or filtration. Additionally, simultaneously with the removal of the acidic catalyst, by-product alcohol or excess water may be removed by methods such as reduced pressure. Furthermore, by diluting with a solvent used for the condensation reaction after removal, it may be easier to add the hydrolysis reaction product in the subsequent condensation reaction.
[0043] In the condensation reaction, water is produced as a byproduct between the above silanol groups, and an alcohol is produced as a byproduct between the silanol groups and the alkoxy groups, thereby forming a siloxane bond. In the condensation reaction, a basic catalyst capable of functioning as a conventionally known dehydration condensation catalyst may be optionally used. Among these, it is preferable that it be highly basic, and specific examples include alkali salts such as sodium hydroxide (NaOH), potassium hydroxide (KOH), and calcium hydroxide (Ca(OH)2); organic amines such as 1,8-diazabicyclo[5.4.0]undeca-7-ene and 1,5-diazabicyclo[4.3.0]nona-5-ene; and ammonium hydroxides such as tetramethylammonium hydroxide and tetrabutylammonium hydroxide. Any of the above example compounds may be used alone or in appropriate combination. Among the above example compounds, tetramethylammonium hydroxide is particularly desirable because it has high catalytic activity and is also easy to obtain. In addition, when these basic catalysts are used as aqueous solutions, since hydrolysis reactions proceed even during the condensation reaction process, it is necessary to make appropriate adjustments, such as reducing the amount of water used during hydrolysis to the amount of water contained in the basic catalyst beforehand.
[0044] The amount of basic catalyst added is preferably 0.01 parts by mass or more and 5 parts by mass or less, with respect to 100 parts by mass of the total of component (a1) and component (a2), and more preferably 0.1 parts by mass or more and 2 parts by mass or less. If the amount added exceeds 5 parts by mass, the cured product made using the obtained component (A) tends to become easily colored, the catalyst cannot be completely removed when removed, or the process of removing the catalyst tends to be prolonged. On the other hand, if the amount added does not satisfy 0.01 parts by mass, there is a tendency for the reaction not to proceed substantially or for the reaction time to be prolonged.
[0045] The reaction temperature can be arbitrarily set according to the reactivity of component (a1) or component (a2). The reaction temperature is typically 40°C or higher and 150°C or lower, and preferably 60°C or higher and 100°C or lower. The condensation reaction is carried out in the presence of a polar solvent. If the reaction is carried out in a non-polar solvent, the silanol groups are not completely consumed, or the system gels due to abnormal high molecular weight. As for the polar solvent, a polar solvent that is compatible with water is preferred, and glycol ethers are particularly preferred. Furthermore, among glycol ethers, dialkyl glycol ether-based solvents are particularly preferred because abnormal high molecular weight as described above is particularly difficult to occur. Examples of dialkyl glycol ether-based solvents that are compatible with water include ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, and diethylene glycol diethyl ether.
[0046] The above condensation reaction is carried out by a method of sequentially adding a solution containing a hydrolyzate obtained from a hydrolysis reaction to a polar solvent to which a dehydration condensation catalyst has been added, set to a reaction temperature. The method of addition can be appropriately selected from various known methods. The time required for addition can be arbitrarily set according to the reactivity of component (a1) or component (a2), respectively, but is usually from 30 minutes to 12 hours.
[0047] The above condensation reaction is preferably carried out by diluting with a solvent such that the concentration of component (a1) (or both if component (a2) is used in combination) in the reaction solution is preferably 2 mass% or more and 80 mass% or less, and more preferably by diluting with a solvent such that the concentration is 15 mass% or more and 60 mass% or less. It is preferable to use a solvent having a boiling point higher than the boiling point of water and alcohol produced by the condensation reaction, as this allows them to be removed by distillation from the reaction system. If the above concentration does not satisfy 2 mass%, the content of component (A) included in the obtained negative-type radioactive resin composition tends to decrease. If the above concentration exceeds 80 mass%, gelation may occur during the reaction, or the molecular weight of the generated component (A) tends to become excessively large.
[0048] It is desirable to remove the catalyst used after the condensation reaction is completed, as this improves the stability of component (A) or the negative-type radioactive resin composition containing component (A). The method for removing the catalyst can be appropriately selected from various known methods depending on the catalyst used. For example, when tetramethylammonium hydroxide is used, it can be removed by methods such as adsorption with a cation exchange resin after the condensation reaction is completed.
[0049] (A) The ingredients may be used as a single type or as a mixture of two or more types.
[0050] (B) Polyfunctional methacrylate
[0051] The carbon-carbon double bond of component (B) reacts with the thiol group of component (A) (en-thiol reaction), but the reaction mechanism varies depending on the type of carbon-carbon double bond and the presence or absence of a radical polymerization initiator.
[0052] In this embodiment, a compound having two or more methacrylate groups in one molecule is suitably used to improve the storage stability of the negative-type radiation-reducing resin composition and to control the curability of the obtained insulating film.
[0053] Specific examples of such polyfunctional methacrylates include polyfunctional methacrylic acid esters, such as difunctional methacrylic acid esters or methacrylic acid esters with three or more functionalities.
[0054] Examples of difunctional methacrylic acid esters include ethylene glycol dimethacrylate, propylene glycol dimethacrylate, diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, etc.
[0055] Examples of methacrylic acid esters with three or more functions include trimethylolpropane trimethacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, dipentaerythritol pentamethacrylate, ditrimethylolpropane tetramethacrylate, a mixture of dipentaerythritol pentamethacrylate and dipentaerythritol hexamethacrylate, dipentaerythritol hexamethacrylate, ethylene oxide-modified dipentaerythritol hexamethacrylate, tri(2-methacryloyloxyethyl)phosphate, succinic acid-modified dipentaerythritol pentamethacrylate, etc. In addition, examples include polyfunctional urethane methacrylate-based compounds obtained by reacting a compound having a straight-chain alkylene group and a dicyclic structure and also having two or more isocyanate groups with a compound having one or more hydroxyl groups in the molecule and also having three, four, or five methacryloyloxy groups. Among these, from the perspective of improving storage stability or curability of the obtained insulating film, pentaerythritol tetramethacrylate, trimethylolpropane trimethacrylate, or ditrimethylolpropane tetramethacrylate are preferred as methacrylic acid esters with four or more functions, and pentaerythritol tetramethacrylate or ditrimethylolpropane tetramethacrylate is more preferred.
[0056] Regarding the content ratio of component (B), it is preferable that the mass ratio of component (B) to component (A) is 1 / 2 or more and 2 / 1 or less. In particular, it is preferable that component (B) is a tetrafunctional methacrylate and the mass ratio of component (B) to component (A) is 1 / 2 or more and 2 / 1 or less. Specifically, in these cases, as a lower limit for the content ratio of component (B), 20 parts by mass is preferable and 50 parts by mass is more preferable per 100 parts by mass of component (A). Meanwhile, as an upper limit for the content ratio of component (B), 200 parts by mass is preferable and 150 parts by mass is more preferable per 100 parts by mass of component (A). By keeping the content ratio of component (B) to component (A) within the above range, it is possible to more effectively improve the various characteristics of the obtained insulating film.
[0057] (B) The ingredients may be used as a single type or as a mixture of two or more types.
[0058] (C) Photopolymerization initiator
[0059] (C) Component is a compound that responds to radiation to generate radicals and initiate polymerization, namely a photoradical polymerization initiator.
[0060] (C) Specific examples of photopolymerization initiators include, for instance, O-acyloxime compounds, α-aminoketone compounds, α-hydroxyketone compounds, acylphosphine oxide compounds, etc.
[0061] As O-acyloxime compounds, for example, 1-[9-ethyl-6-(2-methylbenzoyl)-9.H.-carbazole-3-yl]-ethane-1-on-oxime-O-acetate, 1-[9-ethyl-6-benzoyl-9.H.-carbazole-3-yl]-octane-1-on-oxime-O-acetate, 1-[9-ethyl-6-(2-methylbenzoyl)-9.H.-carbazole-3-yl]-ethane-1-on-oxime-O-benzoate, 1-[9-n-butyl-6-(2-ethylbenzoyl)-9.H.-carbazole-3-yl]-ethane-1-on-oxime-O-benzoate, Ethanol,1-[9-ethyl-6-(2-methyl-4-tetrahydrofuranylbenzoyl)-9.H.-carbazole-3-yl]-,1-(O-acetyloxime), Ethanol,1-[9-ethyl-6-(2-methyl-4-tetrahydrofuranylbenzoyl)-9.H.-carbazole-3-yl]-,1-(O-acetyloxime), Ethanol,1-[9-ethyl-6-(2-methyl-5-tetrahydrofuranylbenzoyl)-9.H.-carbazole-3-yl]-,1-(O-acetyloxime), Examples include ethanol, 1-[9-ethyl-6-{2-methyl-4-(2,2-dimethyl-1,3-dioxoranyl)methoxybenzoyl}-9.H.-carbazole-3-yl]-, 1-(O-acetyloxime), ethanol, 1-[9-ethyl-6-(2-methyl-4-tetrahydrofuranylmethoxybenzoyl)-9.H.-carbazole-3-yl]-, 1-(O-acetyloxime), 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], etc.
[0062] Examples of α-aminoketone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholine-4-yl-phenyl)-butan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-(dimethylamino)-1-(4-morpholinophenyl)-2-benzyl-1-butanone, and 1-[4-(2-hydroxyethylsulfanyl)phenyl]-2-methyl-2-(4-morpholino)propan-1-one.
[0063] Examples of α-hydroxyketone compounds include 1-phenyl-2-hydroxy-2-methylpropan-1-one, 1-(4-i-propylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexylphenylketone, etc.
[0064] Examples of acylphosphine oxide compounds include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0065] (C) As a photopolymerization initiator, O-acyloxime compounds, α-aminoketone compounds and acylphosphine oxide compounds are preferred in terms of further promoting the curing reaction by radiation, O-acyloxime compounds and α-aminoketone compounds are more preferred, and O-acyloxime compounds are even more preferred.
[0066] Oxime-based photopolymerization initiators, such as O-acyloxime compounds, generate radicals such as phenyl radicals or methyl radicals when irradiated with light, and polymerization proceeds appropriately through these radicals. Among such oxime-based photopolymerization initiators, oxime-based photopolymerization initiators that generate methyl radicals are preferred in that they have a high initiation efficiency of the polymerization reaction. Furthermore, from the perspective of carrying out the polymerization reaction more efficiently, it is desirable to use a photopolymerization initiator capable of efficiently utilizing ultraviolet light with a wavelength of 350 nm or more. Examples of such oxime ester-based polymerization initiators that generate methyl radicals include compounds having a structure represented by the following formula (1).
[0067]
[0068] In the above formula (1), * indicates a bonding site with another part in the compound.
[0069] By applying an oxime ester-based photopolymerization initiator that generates methyl radicals, it is desirable in that it has excellent curability, development resistance, suppression effect of pattern breakage, and excellent cured film properties even under low-temperature curing conditions.
[0070] As oxime ester-based photopolymerization initiators that generate alkyl radicals including methyl radicals, ethanol, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(o-acetyloxime) (trade name: Yirgacure OXE-02, manufactured by BASF), methanol, [8-[[(acetyloxyl)imino][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methyl]-11-(2-ethylhexyl)-11H-benzo[a]carbazole-5-yl]-, (2,4,6-trimethylphenyl) (trade name: Yirgacure OXE-03, manufactured by BASF), Ethanol, 1-[9-ethyl-6-(1,3-dioxolan, 4-(2-methoxyphenoxy)-9H-carbazole-3-yl]-, 1-(o-acetyloxime) (trade name ADEKA OPT-N-1919, manufactured by ADEKA), Methanol, (9-ethyl-6-nitro-9H-carbazole-3-yl)[4-(2-methoxy-1-methylethoxy-2-methylphenyl]-, o-acetyloxime (trade name ADEKA Arcles NCI-831, manufactured by ADEKA), 1-propanol, 3-cyclopentyl-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(o-acetyloxime) (trade name TR-PBG-304, manufactured by Joshu Kyoryoku Denshi Shinzairyo), 1-Propanone, 3-cyclopentyl-1-[2-(2-pyrimidinylthio)-9H-carbazole-3-yl]-, 1-(o-acetyloxime) (trade name TR-PBG-314, manufactured by Joshu Kyoryoku Denshi Shinzairyo), Ethanol, 2-cyclohexyl-1-[2-(2-pyrimidinyloxy)-9H-carbazole-3-yl]-, 1-(o-acetyloxime) (trade name TR-PBG-326, manufactured by Joshu Kyoryoku Denshi Shinzairyo), Ethanol, 2-cyclohexyl-1-[2-(2-pyrimidinylthio)-9H-carbazole-3-yl]-, 1-(o-acetyloxime) (trade name TR-PBG-331, manufactured by Joshu Kyoryoku Denshi Shinzairyo), Examples include 1-octanone, 1-[4-[3-[1-[(acetyloxy)imino]ethyl]-6-[4-[(4,6-dimethyl-2-pyrimidinyl)thio]-2-methylbenzoyl]-9H-carbazole-9-yl]phenyl]-,1-(o-acetyloxime) (trade name: EXTA-9, manufactured by Union Chemical).
[0071] In addition, a photopolymerization initiator having a tertiary amine structure may be used in combination with an oxime ester-based photopolymerization initiator. This is because the photopolymerization initiator having a tertiary amine structure has a tertiary amine structure that is an oxygen quencher within the molecule, so the radicals generated from the initiator are difficult to deactivate by oxygen, thereby improving sensitivity. Examples of commercially available photopolymerization initiators having the above tertiary amine structure include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (e.g., Yirgacure 907, manufactured by BASF), 2-benzyl-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone (e.g., Yirgacure 369, manufactured by BASF), and 4,4'-bis(diethylamino)benzophenone (e.g., Hycure ABP, manufactured by Kawaguchi Yakuhin).
[0072] As described above, component (C) may be used alone or in a mixture of two or more types. The content ratio of component (C) is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of component (A), and more preferably 5 parts by mass or more and 30 parts by mass or less. By having the above content ratio of 1 part by mass or more and 40 parts by mass or less, the negative-type radiation-reducing resin composition enables the formation of a cured film having high solvent resistance, high hardness, and high adhesion even at low exposure amounts. As a result, an insulating film with superior properties is provided.
[0073] (F) Organic solvent
[0074] The negative-type radiation-reducing resin composition may additionally contain (F) an organic solvent. (F) The organic solvent is not particularly limited and may include, for example, alcohol-based solvents, ether-based solvents, ester-based solvents, ketone-based solvents, amide-based solvents, etc. (F) The organic solvent may be used alone or in combination of two or more types.
[0075] Examples of alcohol-based solvents include alkyl alcohols such as methanol, ethanol, isopropyl alcohol, 1-butanol, 2-butanol, isobutyl alcohol, t-butyl alcohol, 1-hexanol, 1-octanol, 1-nonanol, 1-dodecanol, 1-methoxy-2-propanol, and diacetone alcohol; aromatic alcohols such as benzyl alcohol.
[0076] Examples of ether-based solvents include ethylene glycol monoalkyl ethers such as diethylene glycol methyl ethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether; propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether; diethylene glycol monoalkyl ethers such as diethylene glycol monomethyl ether and diethylene glycol monoethyl ether; diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether and diethylene glycol ethyl methyl ether; and dipropylene glycol monoalkyl ethers such as dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, and dipropylene glycol monobutyl ether.
[0077] Examples of ester-based solvents include carboxylic acid esters such as ethyl acetate, i-propyl acetate, n-butyl acetate, amyl acetate, ethyl lactate, methyl 3-methoxypropionate, and ethyl 3-ethoxypropionate; polyhydric alcohol carboxylate-based solvents such as propylene glycol diacetate; and polyhydric alcohol moiety ether carboxylate-based solvents such as propylene glycol monomethyl ether acetate and propylene glycol monoethyl ether acetate.
[0078] Examples of ketone-based solvents include acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisobutyl ketone, cyclopentanone, cyclohexanone, cycloheptanone, etc.
[0079] Among these, ether-based solvents and ester-based solvents are preferred, ester-based solvents are more preferred, and polyhydric alcohol portion ethercarboxylate-based solvents are even more preferred. In addition, among ether-based solvents and ester-based solvents, diethylene glycol dimethyl ether, diethylene glycol ethylmethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monomethyl ether acetate, and 3-methyl methoxypropionate are preferred.
[0080] The content of (F) organic solvent in the negative-type radiation-reducing resin composition is not particularly limited, but it is preferable to prepare it so that the concentration of solids (components other than (F) organic solvent) is within the following range. As a lower limit for the solid concentration in the negative-type radiation-reducing resin composition, 5 mass% is preferable, 10 mass% is more preferable, and 20 mass% is even more preferable. Meanwhile, as an upper limit for this solid concentration, 60 mass% is preferable, 50 mass% is more preferable, and 40 mass% is even more preferable.
[0081] (D) UV absorber
[0082] The negative-type radiation-reducing resin composition may additionally contain (D) an ultraviolet absorber (hereinafter also referred to as "component (D)"). Component (D) is added for the purpose of controlling the photocuring distribution by absorbing a specific wavelength of the light source used for exposure through component (D). By including component (D) in the negative-type radiation-reducing resin composition, effects such as improving the taper angle shape after development or reducing residue remaining in the non-exposed area after development tend to be obtained. As component (D), a compound having an absorption maximum between a wavelength of 250 nm and 400 nm may be used, for example, from the perspective of inhibiting light absorption by component (C).
[0083] (D) Examples of components include benzotriazole compounds, triazine compounds, benzophenone compounds, benzoate compounds, cinnamic acid derivatives, naphthalene derivatives, anthracene and its derivatives, dinaphthalene compounds, phenanthroline compounds, dyes, etc.
[0084] (D) The component may be used alone or in combination of two or more types.
[0085] Among these, benzotriazole compounds and / or hydroxyphenyltriazine compounds are preferred from the perspective of increasing the taper angle, and benzotriazole compounds are particularly preferred. Specifically, examples of benzotriazole compounds include 2-(5-t-butyl-2-hydroxyphenyl)benzotriazole, 2,2-methylenebis{6-(benzotriazole-2-yl-4-tert-octylphenol)}, etc. Examples of benzophenone-based organic compounds include 2,2-di-hydroxy-4,4-dimethoxybenzophenone, etc. Examples of triazine-based organic compounds include 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine, etc. Available commercial products include BASF’s “TINUVIN PS”, “TINUVIN P”, “TINUVIN 324”, “TINUVIN 326”, “TINUVIN 360”, Ciprocasey’s “Sisov 107”, and ADEKA’s “Adecastav LA-F70”.
[0086] (D) The content ratio of the component is preferably 0.1 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the component (A), more preferably 1 part by mass or more and 30 parts by mass or less, even more preferably 10 parts by mass or more and 30 parts by mass or less, and even more preferably 20 parts by mass or more and 30 parts by mass or less. By satisfying the above ranges for the content ratio, the shape and resolution of the pattern obtained are improved.
[0087] (E) Base generator
[0088] The negative-type radioactive resin composition may additionally contain (E) a base-generating agent (hereinafter also referred to as “(E) component”).
[0089] (E) As for base generating agents, they are not particularly limited as long as they are compounds that generate a base (such as an amine) upon irradiation with radiation. (E) Examples of base generating agents include transition metal complexes such as cobalt, orthonitrobenzyl carbamates, α,α-dimethyl-3,5-dimethoxybenzyl carbamates, acyloxyiminos, etc.
[0090] Examples of transition metal complexes of the above include bromopentammonia cobalt perchlorate, bromopentamethylamine cobalt perchlorate, bromopentapropylamine cobalt perchlorate, hexaammonia cobalt perchlorate, hexamethylamine cobalt perchlorate, hexapropylamine cobalt perchlorate, etc.
[0091] Examples of orthonitrobenzyl carbamates include [[(2-nitrobenzyl)oxy]carbonyl]methylamine, [[(2-nitrobenzyl)oxy]carbonyl]propylamine, [[(2-nitrobenzyl)oxy]carbonyl]hexylamine, [[(2-nitrobenzyl)oxy]carbonyl]cyclohexylamine, etc.
[0092] Examples of α,α-dimethyl-3,5-dimethoxybenzyl carbamates include [[(α,α-dimethyl-3,5-dimethoxybenzyl)oxy]carbonyl]methylamine, [[(α,α-dimethyl-3,5-dimethoxybenzyl)oxy]carbonyl]propylamine, etc.
[0093] Examples of acyloxyimino compounds include propionylacetophenone oxime, propionylbenzophenone oxime, propionylacetone oxime, butyrylacetophenone oxime, butyrylbenzophenone oxime, butyrylacetone oxime, adipoylacetophenone oxime, adipoylbenzophenone oxime, etc.
[0094] Other examples of base-generating agents other than those mentioned above include 2-nitrobenzylcyclohexylcarbamate, O-carbamoylhydroxyamide, and O-carbamoylhydroxyamide 1,2-diisopropyl-3-{bis(dimethylamino)methylene}guanidium=2-(3-benzoylphenyl)propionate.
[0095] (E) One type of base generating agent may be used alone, or two or more types may be used in combination.
[0096] (E) As a lower limit for the content ratio of the base generating agent, 0.1 parts by mass is preferred and 1 part by mass is more preferred per 100 parts by mass of component (A). (E) As an upper limit for the content ratio of the base generating agent, 20 parts by mass is preferred and 10 parts by mass is more preferred per 100 parts by mass of component (A). By satisfying the above ranges for the content ratio, the resulting pattern shape and heat resistance are improved to a high level.
[0097] (Other ingredients)
[0098] The negative-type radiation-reducing resin composition may additionally contain other components other than the aforementioned components (A), (B), (C), (D), (E), and (F) organic solvent. Examples of such other components include curing agents, curing accelerators, adhesion aids, antioxidants, surfactants, etc. However, regarding the content of other components other than components (A), (B), (C), (D), (E), and (F) organic solvent in the negative-type radiation-reducing resin composition, it is preferable to have 10 mass% or less, and it is more preferable to have 1 mass% or less.
[0099] (Viscosity of negative-type radioactive resin composition)
[0100] The viscosity of the negative-type radiation-reducing resin composition, measured using an E-type viscometer under conditions of 25°C and 50 rpm, is preferably 0.5 mPa·s or more and 20 mPa·s or less, more preferably 0.5 mPa·s or more and 7 mPa·s or less, and even more preferably 2.5 mPa·s or more and 5 mPa·s or less. By satisfying the above ranges for viscosity, all of the resolution, residual film rate, chemical resistance, oxygen ashing resistance, and storage stability described below are excellent. The viscosity of the negative-type radiation-reducing resin composition can be set to the above range by adjusting the amount of (F) organic solvent added.
[0101] <Temperature for forming a hardened film>
[0102] The negative-type radiation-reducing resin composition can obtain a cured film having sufficient resistance to etching agents and oxygen ashing even by heating at a relatively low temperature, as described above. The negative-type radiation-reducing resin composition is preferably a composition that can be cured by heating in a temperature range of, for example, 60°C or higher and 120°C or lower, and is more preferably a composition that can be cured by heating in a temperature range of 60°C or higher and 100°C or lower.
[0103] Method for preparing a negative-type radioactive resin composition
[0104] The negative-type radiation-reducing resin composition can be prepared by mixing each component in a predetermined ratio and dissolving it in an organic solvent (F). It is preferable to filter the prepared composition, for example, with a filter having a pore size of about 0.2 μm.
[0105] Insulating film for organic EL devices
[0106] An insulating film for an organic EL device according to one embodiment of the present invention is a cured film formed by the said negative-type radiation-reducing resin composition. The insulating film for the said organic EL device may be a patterned film. Since the insulating film for the said organic EL device is formed by a negative-type radiation-reducing resin composition that can obtain a cured film having sufficient resistance to etching agents and oxygen ashing resistance even by heating at a relatively low temperature, it has a high yield and excellent durability.
[0107] The insulating film for the organic EL device is suitable as an interlayer insulating film, and may also be used as a planarization film, a spacer, a protective film, etc. The insulating film for the organic EL device can also be used in a display device equipped with an organic EL device (organic EL device), electronic paper, etc. Furthermore, as described below, the insulating film for the organic EL device is suitable as an interlayer insulating film between a touch panel and another layer in a display device equipped with a touch panel, such as an organic EL device equipped with a touch panel.
[0108] The insulating film for the organic EL device is unlikely to develop cracks even when relatively thick. Therefore, the insulating film for the display device can be made thick. As for the lower limit of the average thickness of the insulating film for the organic EL device, for example, 0.1 μm is preferable, 0.5 μm is more preferable, 1 μm is more preferable, and 2 μm is even more preferable. On the other hand, as for the upper limit of this average thickness, for example, 10 μm is acceptable, 6 μm is acceptable, and 4 μm is acceptable.
[0109] The insulating film for the organic EL device described above may be provided in various display devices. Examples of such display devices include organic EL devices and electronic paper, and among these, organic EL devices are preferred.
[0110] Organic EL Device
[0111] An organic EL device according to one embodiment of the present invention comprises the aforementioned insulating film for the organic EL element. The organic EL device preferably comprises a touch panel laminated on a substrate having an organic EL element. The organic EL element typically has a laminated structure comprising an anode layer, an organic light-emitting layer, and a cathode layer. It is preferable that the insulating film for the organic EL element be used in at least a portion of the insulating film in the touch panel. In particular, it is preferable that the insulating film for the organic EL element be used in the insulating film of the touch panel laminated on a substrate having an organic EL element without passing through an adhesive layer or an adhesive layer. By doing so, since the touch panel can be directly laminated on a substrate having an organic EL element, it becomes possible to thin the organic EL device having the touch panel.
[0112] Since the said negative-type radiation-reducing resin composition can obtain a cured film having sufficient resistance to etching agents and oxygen ashing even by heating at a relatively low temperature, it is possible to suppress the degradation of organic EL elements in the manufacturing process of the said organic EL device and increase the yield. In addition, since the degradation of organic EL elements in the manufacturing process can be suppressed by forming an insulating film by heating at a relatively low temperature using the said negative-type radiation-reducing resin composition, the said negative-type radiation-reducing resin composition can be particularly suitable for forming an insulating film in various organic EL devices equipped with organic EL elements, other than organic EL devices equipped with touch panels.
[0113] FIG. 1 illustrates an organic EL device having a touch panel. The organic EL device (10) with a touch panel attached according to FIG. 1 comprises an organic EL display substrate (20) and a touch panel (30). The organic EL display substrate (20) has a structure in which a support substrate (21), an anode layer (22), an organic light-emitting layer (23), a cathode layer (24), an adhesive layer (25), and an encapsulation substrate (26) are stacked in this order. Additionally, at least the anode layer (22), the organic light-emitting layer (23), and the cathode layer (24) constitute an organic EL element. As for the organic light-emitting layer (23), for example, a structure in which a hole injection layer, a hole transport layer, an organic EL light-emitting layer, an electron transport layer, and an electron injection layer are stacked in this order from the anode layer (22) side may be adopted.
[0114] The touch panel (30) is of the capacitive type, wherein a first sensor electrode (31), an insulating film (33), and a second sensor electrode (32) are stacked in this order. The touch panel (30) has a first sensor electrode (31), a second sensor electrode (32) positioned facing the first sensor electrode (31), an insulating film (33), and a transparent substrate (34) positioned on the outermost surface. In this embodiment, the first sensor electrode (31) is formed directly on the encapsulation substrate (26) of the organic EL display substrate (20). The insulating film (33) is a transparent insulating film that insulates the first sensor electrode (31) and the second sensor electrode (32), and is formed from the negative type radiation-reducing resin composition. Furthermore, the touch panel is not limited to this capacitive type.
[0115] Method for Forming an Insulating Film for Organic EL Devices
[0116] A method for forming an insulating film for an organic EL device according to one embodiment of the present invention comprises: a process of forming a film by applying the aforementioned negative-type radiation-sensitive resin composition directly or indirectly onto a substrate (hereinafter also referred to as a "film forming process"); a process of irradiating (exposing) at least a portion of the film with radiation after the process of forming the film (hereinafter also referred to as a "radiation irradiation process"); a process of developing the film after the process of irradiating radiation (hereinafter also referred to as a "developing process"); and a process of heating the film at a temperature of 60°C or higher and 120°C or lower after the developing process (hereinafter also referred to as a "heating process"). As an optional process, the forming method may include a process of heating the film (hereinafter also referred to as a "PEB process") between the radiation irradiation process and the developing process.
[0117] According to the formation method, since the aforementioned negative-type radiation-reducing resin composition is used, it is possible to pattern it into a good shape, and an insulating film having sufficient resistance to etching agents and oxygen ashing can be obtained even by heating at a relatively low temperature. Furthermore, even if the substrate on which the film is formed includes an organic EL element, it becomes possible to suppress the degradation of the organic EL element by performing the heating process at a relatively low temperature. Each process will be described below.
[0118] (Film formation process)
[0119] In this process, the negative-type radiation-reducing resin composition is applied directly onto a substrate or through another layer, and then, preferably, the coated surface is heated (prebaked) to remove organic solvents, etc., thereby forming a coating film. Examples of the material of the substrate include glass, quartz, silicon, resin, etc. Specific examples of the resin include polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethersulfone, polycarbonate, polyimide, addition polymer of cyclic olefin, ring-opening polymer of cyclic olefin, and hydrogenated derivatives thereof.
[0120] The above substrate may include an organic EL element, etc. Additionally, the above substrate may have electrodes, wiring, etc. formed on the coated surface. As such a substrate, an organic EL display substrate (20) having a first sensor electrode (31) formed thereon as shown in FIG. 1 above can be exemplified.
[0121] The application method of the negative-type radiation-reducing resin composition is not particularly limited, and suitable methods such as spraying, roll coating, spinning (spin coating), slit die coating, and bar coating may be employed. Among these application methods, spin coating and slit die coating are particularly preferred. The conditions for pre-baking vary depending on the type and mixing ratio of each component, but for example, it is preferable to heat at a temperature of 60°C or higher and 120°C or lower, more preferably 100°C or lower, for a heating time of 1 minute or more and 10 minutes or less.
[0122] (Radiation irradiation process)
[0123] In this process, radiation is irradiated onto at least a portion of the coating formed in the coating formation process. Typically, when irradiating a portion of the coating with radiation, the radiation is irradiated through a photomask having a predetermined pattern. Examples of the radiation may include visible light, ultraviolet light, far-ultraviolet light, electron beams, X-rays, etc. Among these radiations, radiation with a wavelength in the range of 190 nm to 450 nm is preferred, and radiation including ultraviolet light of 365 nm is more preferred.
[0124] As a lower limit for the exposure amount in this process, the value measured by an illuminance meter (OAI Optical Associates Inc.’s “OAI model 356”) for the intensity at a radiation wavelength of 365 nm is preferably 10 mJ / cm², and more preferably 50 mJ / cm². In addition, as an upper limit for the exposure amount, the value measured by the illuminance meter is preferably 2,000 mJ / cm², and more preferably 1,000 mJ / cm².
[0125] (PEB process)
[0126] When forming the PEB process, the PEB conditions vary depending on the type and mixing ratio of each component, but for example, it is preferable to heat at a temperature of 60°C or higher and 120°C or lower, more preferably 100°C or lower, for a heating time of 1 minute or more and 10 minutes or less.
[0127] (Development Process)
[0128] In this process, a predetermined pattern is formed by developing the coating film after radiation irradiation with a developer. An alkaline developer is preferred as the developer. Examples of alkaline developers include an alkaline aqueous solution in which at least one alkaline compound, such as sodium hydroxide, potassium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, ammonia, tetramethylammonium hydroxide, and tetraethylammonium hydroxide, is dissolved. Additionally, an appropriate amount of a water-soluble organic solvent, such as methanol or ethanol, or a surfactant may be added to the alkaline developer.
[0129] As a development method, appropriate methods such as the puddle method, dipping method, shaking immersion method, and spray method may be employed. The development time varies depending on the composition of the radioactive composition, but is, for example, 10 seconds or more and 180 seconds or less. Following this development process, for example, a water wash may be performed for a treatment time of 30 seconds or more and 90 seconds or less, and then air-dried, for example, with compressed air or compressed nitrogen, to form a desired pattern.
[0130] (Heating process)
[0131] In this process, an insulating film for a display device having a desired pattern is obtained by heating (post-baking) a developed and patterned film using a heating device such as a hot plate or an oven. Additionally, between the development process and the heating process, the film may be irradiated with radiation such as ultraviolet rays. The exposure amount at this time may be, for example, 100 mJ / cm² or more and 2,000 mJ / cm² or less. The lower limit of the heating temperature is 60°C, and 80°C is preferred. By setting the heating temperature above the lower limit, a sufficiently cured insulating film can be obtained. Meanwhile, the upper limit of the heating temperature is 120°C, and 100°C is preferred. By setting the heating temperature above the lower limit, a sufficiently cured insulating film can be obtained while suppressing the degradation of, for example, an organic EL element provided on a substrate. In addition, by keeping the heating temperature below the upper limit mentioned above, the occurrence of excessive stress, such as rapid film shrinkage, can be suppressed, thereby preventing the occurrence of cracks. Accordingly, in the heating process, heating is performed within a temperature range of 60°C to 120°C. The heating time varies depending on the type of heating device, but for example, when heating on a hot plate, it should be 5 minutes to 30 minutes, and when heating in an oven, it should be 10 minutes to 90 minutes. Furthermore, heating may be performed in air or in an inert gas atmosphere such as nitrogen or argon. It is also possible to use a step baking method that performs two or more heating processes.
[0132] (Other processes)
[0133] When manufacturing the said organic EL device, after forming an insulating film for the said organic EL element on an organic EL display substrate, other processes are performed, such as forming additional electrodes, wiring, etc. (e.g., the second sensor electrode (32) in the touch panel (30) of FIG. 1). Examples of such processes include an electrode formation process, a wiring formation process, an etching process, and an ashing process. Known methods such as printing or deposition may be employed for forming electrodes or wiring. Etching may be performed using a known etching solution, such as an amine-based solution. Ashing may be performed by a known ashing method, such as oxygen ashing. Furthermore, when manufacturing the touch panel, etc., the formation of the insulating film, electrodes, wiring, etc., may each be performed multiple times.
[0134] [Example]
[0135] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.
[0136] <Measurement of Weight-Average Molecular Weight (Mw)>
[0137] In the polymer synthesis examples shown below, the weight average molecular weight (Mw) of the obtained polymer was measured by gel permeation chromatography (GPC) under the following conditions.
[0138] Device: Showa Denko's "GPC-101"
[0139] Column: A combination of Showa Denko's "GPC-KF-801," "GPC-KF-802," "GPC-KF-803," and "GPC-KF-804"
[0140] Mobile phase: Tetrahydrofuran
[0141] Column temperature: 40℃
[0142] Flow rate: 1.0 mL / min
[0143] Sample concentration: 1.0 mass%
[0144] Sample injection volume: 100μL
[0145] Detector: Parallax Refractometer
[0146] Standard material: Monodisperse polystyrene
[0147] Viscosity Measurement
[0148] The viscosity is a value measured at 25°C using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) in accordance with JIS K2283:2000.
[0149] Below, an example of synthesis of a thiol group-containing polysiloxane as component (A) is presented. Additionally, unless otherwise specifically stated below, “%” means “mass%”.
[0150] [Synthesizing Example 1] (Preparation of thiol group-containing polysiloxane solution (A-1))
[0151] In a reaction apparatus equipped with a stirrer, a cooling tube, a water dispenser, a thermometer, and a nitrogen inlet, 190 g of 3-mercaptopropyltrimethoxysilane (manufactured by Shin-Etsu Kagaku Kogyo Co., Ltd.: trade name "KBM-803") as component (a1), 52.3 g of ion-exchanged water ([moles of water used for the hydrolysis reaction] / [moles of alkoxy groups contained in component (a1)] (molar ratio) = 1.0), and 9.5 g of 95% formic acid were added, and a hydrolysis reaction was carried out at room temperature for 30 minutes. During the reaction, the temperature rose to a maximum of 22°C due to exothermic reaction. After the reaction, 287.36 g of propylene glycol monomethyl ether acetate was added, and the mixture was heated. At the point when the temperature was raised to 82°C, methanol generated by hydrolysis began to be removed by distillation. The temperature was raised to 105°C over 30 minutes, and the water generated by the condensation reaction was removed by distillation. Additionally, after reacting at 105°C for 1 hour and 30 minutes, the pressure was reduced to 70°C-150 mmHg to remove some of the remaining methanol, water, formic acid, and propylene glycol monomethyl ether acetate by distillation, thereby obtaining 385.2 g of condensate solution (A-1). In the thiol group-containing polysiloxane (component (A-1)) contained in the condensate solution (A-1), the [total number of moles of unreacted hydroxyl groups and unreacted alkoxy groups] / [number of moles of alkoxy groups contained in component (a1)] (molar ratio) was 0.15, and the concentration was 32.0%. Furthermore, the thiol equivalent of the condensate solution (A-1) was 398 g / eq, and the Mw was 2147.
[0152] [Synthesizing Example 2] (Preparation of thiol group-containing polysiloxane solution (A-2))
[0153] In a reaction apparatus equipped with a stirrer, a cooling tube, a fountain, a thermometer, a dropping lot, and a nitrogen blower, 300g of 3-mercaptopropyltrimethoxysilane (manufactured by Shin-Etsu Kagaku Kogyo Co., Ltd.: product name "KBM-803") as component (a1), 162.8g of ion-exchanged water ([moles of water used for the hydrolysis reaction] / [moles of alkoxy groups included in component (a1)] (molar ratio) = 2.0), and 6.0g of cation exchange resin (manufactured by Mitsubishi Kagaku Co., Ltd.: product name "Diion PK228LH", H-type strong acid cation exchange resin) were added, and a hydrolysis reaction was carried out at room temperature for 30 minutes. During the reaction, the temperature rose to a maximum of 28℃ due to exothermic reaction. After the reaction, the cation exchange resin was filtered, and 228 g of hydrolysate was obtained by reducing the pressure to 70°C and 20 kPa for 3 hours. This was diluted with 82 g of ethylene glycol dimethyl ether to obtain a 310 g hydrolysate solution.
[0154] Next, 325.9 g of ethylene glycol dimethyl ether and 1.25 g of a 25% aqueous solution of tetramethylammonium hydroxide were added to another reaction vessel, and the mixture was heated to 80°C. Since tetramethylammonium hydroxide did not dissolve in ethylene glycol dimethyl ether, the mixture became slightly cloudy. To this, 300 g of the hydrolysate solution obtained above was added dropwise over a period of 2 hours and 30 minutes. During the dropwise addition, tetramethylammonium hydroxide dissolved, and the reaction solution became clear. After the dropwise addition, the mixture was reacted at 80°C for another 15 minutes, and then cooled to 25°C. At 25°C, tetramethylammonium hydroxide did not dissolve, and the reaction solution became slightly cloudy. To this, 6.4 g of the same cation exchange resin as above was added, and the mixture was stirred at room temperature for 4 hours. During stirring, tetramethylammonium hydroxide was adsorbed onto the cation exchange resin, and the reaction solution became clear. After filtration of the cation exchange resin, 196 g of a thiol group-containing polysiloxane solution (A-2) was obtained by reducing the pressure at 70°C and 20 kPa for 2 hours, and then at 70°C and 0.7 kPa for 1 hour. As a result of analyzing the thiol group-containing polysiloxane (component (A-2)) contained in the solution (A-2) by infrared spectroscopy, at 3500 cm⁻¹ -1 There was no absorption of silanol groups visible in the vicinity. Additionally, no silanol groups were observed in analysis by nuclear magnetic resonance. The [total number of moles of unreacted hydroxyl groups and unreacted alkoxy groups] / [number of moles of alkoxy groups included in component (a1)] (molar ratio) for component (A-2) was 0. Furthermore, the concentration of component (A-2) in solution (A-2) was 94.7%, the thiol equivalent was 133 g / eq, and the Mw was 2700.
[0155] [Preparation of a negative-type radioactive resin composition]
[0156] The raw materials used in the preparation of each negative-type radioactive resin composition are shown below.
[0157] (A) Ingredient
[0158] A-1: Thiol group-containing polysiloxane obtained in Synthesis Example 1
[0159] A-2: Thiol group-containing polysiloxane obtained in Synthesis Example 2
[0160] A-3: Thiol group-containing polysiloxane (Compoceran SQ109 manufactured by Arakawa Kagaku Kogyo Co., Ltd.)
[0161] (a) Comparative component
[0162] a-1: Pentaerythritol tetrakis(3-mercaptopropionate)(PEMP)
[0163] (B) Component
[0164] B-1: Pentaerythritol tetramethacrylate
[0165] B-2: Ditrimethylolpropane tetramethacrylate
[0166] B-3: Trimethylolpropane trimethacrylate
[0167] (b) Comparative component
[0168] b-1: Dipentaerythritol hexaacrylate (DPHA)
[0169] (C) Component
[0170] C-1: 1,2-octanedione, 1-{4-(phenylthio)phenyl}-, 2-(O-benzoyloxime) (BASF IRGACURE OXE-01)
[0171] C-2: NCI-930 (manufactured by ADEKA)
[0172] C-3: 2-methyl-1-{4-(methylthio)phenyl}-2-morpholinopropane-1-one (BASF IRGACURE907)
[0173] (D) Component
[0174] D-1: TinuvinPS (manufactured by BASF)
[0175] D-2: Tinuvin324 (Manufactured by BASF)
[0176] (E) Component
[0177] E-1: 1,2-diisopropyl-3-{bis(dimethylamino)methylene}guanidium=2-(3-benzoylphenyl)propionate
[0178] (F) Organic solvent
[0179] F-1: Propylene glycol monomethyl ether acetate (PGMEA)
[0180] Examples of preparations for negative-type radioactivity-reducing resin compositions are presented below. Additionally, unless otherwise specified, "%" means "mass%".
[0181] (Example 1)
[0182] The negative-type radiation-reducing resin composition of Example 1 was prepared by dissolving 100 parts by mass of (A-1) as component (A), 200 parts by mass of (B-1) as component (B), 15 parts by mass of (C-1) as component (C), and 20 parts by mass of (D-2) as component (D) in 500 parts by mass of (F-1) as organic solvent (F) of the solution (A-1) obtained in Synthesis Example 1. For the obtained negative-type radiation-reducing resin composition, the viscosity measured using an E-type viscometer under conditions of 25°C and 50 rpm was 3.5 mPa·s. The results are shown in Table 1.
[0183] (Examples 2 to 11, Comparative Examples 1 to 2)
[0184] Except for using each component of the type and content shown in Table 1, negative-type radiation-reducing resin compositions of Examples 2 to 11 and Comparative Examples 1 to 2 were prepared in the same manner as in Example 1, and the viscosity of the obtained negative-type radiation-reducing resin compositions was measured in the same manner as in Example 1. The results are shown in Table 1.
[0185] [evaluation]
[0186] For the negative-type radioactivity-reducing resin composition obtained above, resolution, residual film rate, chemical resistance, oxygen ashing resistance, and storage stability were evaluated according to the following methods. The results are shown in Table 1.
[0187] Resolution
[0188] A negative-type radioactive resin composition was applied by spin coating onto a silicon substrate, and then pre-baked on a hot plate at 85°C for 2 minutes to form a film with a thickness of 2.5 μm. The obtained film was exposed using a high-pressure mercury lamp (exposure amount at 365 nm: 100 mJ / cm²) through a mask in which square extraction patterns with sides of 10 μm were arranged at 10 μm intervals, and then developed by the puddle method in an aqueous solution of 2.38 mass% tetramethylammonium hydroxide at 25°C for 60 seconds. Subsequently, a pattern was formed on the silicon substrate by washing with ultrapure water for 60 seconds and then drying. The square sample pattern with sides of 10 μm obtained in this way was observed for cross-sectional shape at a magnification of 1500x using a scanning electron microscope (S-4200 manufactured by Hitachi Seisakusho Inc.). A pattern opening formed without residuals was evaluated as good and indicated as "A," and a pattern opening with residuals was evaluated as poor and indicated as "B."
[0189] Residual rate
[0190] A negative-type radioactive resin composition was applied to a silicon substrate by spin coating, and then pre-baked on a hot plate at 85°C for 2 minutes to form a film with a thickness of 2.5 μm. The obtained film was exposed to light on its entire surface using a high-pressure mercury lamp (exposure amount at 365 nm is 100 mJ / cm²), and then developed by the puddle method in a 2.38 mass% aqueous solution of tetramethylammonium hydroxide at 25°C for 60 seconds. Subsequently, the film was formed on the silicon substrate by washing with ultrapure water for 60 seconds and then drying. The average film thickness before and after development was measured, and the residual film rate (residual film rate before and after development) was calculated based on the following formula (1). This residual film rate was evaluated according to the following criteria. That is, if the film residue rate is 85% or higher, it is evaluated as extremely good and indicated as “A”; if the film residue rate is 80% or higher and less than 85%, it is evaluated as very good and indicated as “B”; if the film residue rate is 75% or higher and less than 80%, it is evaluated as good and indicated as “C”; and if the film residue rate is less than 75%, it is evaluated as poor and indicated as “D”.
[0191] Residual film percentage (%) = {(Average film thickness after development) / (Average film thickness before development)} × 100 ··· (Formula 1)
[0192] Chemical Resistance
[0193] A negative-type radioactive resin composition was applied by spin coating onto a silicon substrate, and then pre-baked on a hot plate at 85°C for 2 minutes to form a film with a thickness of 2.5 μm. The obtained film was exposed to light on the entire surface using a high-pressure mercury lamp (exposure amount at 365 nm: 100 mJ / cm²), and then developed by the puddle method in an aqueous solution of 2.38 mass% tetramethylammonium hydroxide at 25°C for 60 seconds. Subsequently, the film was formed on the silicon substrate by washing with ultrapure water for 60 seconds and then drying. Subsequently, the entire surface was exposed to light using a high-pressure mercury lamp (exposure amount at 365 nm: 200 mJ / cm²), and then post-baked in an oven at 85°C for 1 hour. The obtained substrate was immersed in a 70 mass% aqueous solution of 2-aminoethanol at 60°C for 5 minutes. The average film thickness before and after immersion was measured, and the ratio of the average film thickness after immersion to the average film thickness before immersion (film thickness ratio before and after immersion) was calculated. This ratio was evaluated according to the following criteria. Specifically, if the film thickness ratio before and after immersion was 97% or more and less than 103%, it was evaluated as extremely good and indicated as "A"; if the film thickness ratio before and after immersion was 95% or more and less than 97%, it was evaluated as very good and indicated as "B"; if the film thickness ratio before and after immersion was 103% or more and less than 105%, it was evaluated as good and indicated as "C"; and if the film thickness ratio before and after immersion was less than 95% or 105% or more, it was evaluated as defective due to peeling of the cured film, etc., and indicated as "D".
[0194] Oxygen Ashing Resistance
[0195] A negative-type radioactive resin composition was applied by spin coating onto a silicon substrate, and then pre-baked on a hot plate at 85°C for 2 minutes to form a film with a thickness of 2.5 μm. The obtained film was exposed to light on the entire surface using a high-pressure mercury lamp (exposure amount at 365 nm: 100 mJ / cm²), and then developed by the puddle method in an aqueous solution of 2.38 mass% tetramethylammonium hydroxide at 25°C for 60 seconds. Subsequently, the film was formed on the silicon substrate by washing with ultrapure water for 60 seconds and then drying. Subsequently, the entire surface was exposed to light using a high-pressure mercury lamp (exposure amount at 365 nm: 100 mJ / cm²), and then post-baked in an oven at 85°C for 1 hour. The film (cured film) formed on the substrate in this manner was ashed under predetermined conditions (300W, 30sec, O230sccm). The average film thickness before and after ashing was measured, and the residual film rate (residual film rate before and after ashing) was calculated based on the following formula (2). Oxygen ashing resistance was evaluated using the calculated residual film rate according to the following criteria. That is, if the residual film rate is 95% or more, it is evaluated as extremely good and indicated as “A”; if the residual film rate is 93% or more and less than 95%, it is evaluated as very good and indicated as “B”; if the residual film rate is 90% or more and less than 93%, it is evaluated as good and indicated as “C”; and if the residual film rate is less than 90%, it is evaluated as poor and indicated as “D”.
[0196] Residual film percentage (%) = {(Average film thickness after ashing) / (Average film thickness before ashing)} × 100 ··· (Equation 2)
[0197] <Preservation Stability>
[0198] 10 mL of a negative-type radioactive resin composition was placed in a screw tube and stored for 3 days under 40°C light shielding. Then, the viscosity before and after storage was measured in the same manner as the viscosity measurement described above, and the viscosity increase rate before and after storage was confirmed based on the following formula (3). If the viscosity increase rate was less than 110%, it was evaluated as good and indicated as “A”, and if the viscosity increase rate was 110% or more, it was evaluated as poor and indicated as “B”.
[0199] Viscosity increase rate (%) = {(Viscosity after storage) / (Viscosity before storage)} × 100%···(Equation 3)
[0200]
[0201] According to the negative-type radiation-reducing resin compositions of Examples 1 to 11, it was found that an insulating film can be formed that has lithographic performance, possesses sufficient hardness even when heated at a relatively low temperature, and does not easily develop cracks such as cracks. In addition, it was confirmed that when forming an insulating film with the negative-type radiation-reducing resin compositions of Examples 1 to 11, the generation of outgas was low, and thus the problem of outgas generation could be reduced. Industrial applicability
[0202] A negative type radiation-reducing resin composition can be suitably used as a material for forming an insulating film used in organic EL devices. Explanation of the symbols
[0203] 10: Organic EL device 20: Organic EL display substrate 21: Support substrate 22 : Anode layer 23: Organic light-emitting layer 24: Cathode layer 25: Adhesive layer 26 : Encapsulation substrate 30: Touch panel 31: First sensor electrode 32: Second sensor electrode 33 : Insulating film 34: Transparent substrate
Claims
Claim 1 A negative-type radiation-reducing resin composition for forming an insulating film for an organic EL device, comprising (A) a polysiloxane having at least one thiol group, (B) a polyfunctional methacrylate (excluding polyfunctional acrylate), and (C) a photopolymerization initiator, wherein the viscosity measured at 25°C and 50 rpm using an E-type viscometer equipped with a cone rotor (1°34'×R24) is 2.5 mPa·s or more and 5.0 mPa·s or less. Claim 2 A negative-type radiation-reducing resin composition according to claim 1, wherein the (B) polyfunctional methacrylate is a methacrylate with four or more functions, and the mass ratio of the (B) polyfunctional methacrylate to the (A) polysiloxane having at least one thiol group is 1 / 2 or more and 2 / 1 or less. Claim 3 A negative-type radiation-reducing resin composition in which the (C) photopolymerization initiator is a compound having a structure represented by the following formula (1). [In the above formula (1), * indicates a bonding site with another part in the compound] Claim 4 A negative-type radiation-reducing resin composition according to claim 1, wherein (D) an ultraviolet absorber is additionally contained, and the content ratio of the (D) ultraviolet absorber is 0.1 parts by weight or more and 30 parts by weight or less per 100 parts by weight of the (A) polysiloxane having at least one thiol group. Claim 5 A negative-type radiation-reducing resin composition according to claim 1, wherein (E) a base generating agent is additionally contained, and the content ratio of the (E) base generating agent is 0.1 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the (A) polysiloxane having at least one thiol group. Claim 6 A method for forming an insulating film for an organic EL device, comprising: a process of forming a film by applying a negative-type radiation-sensitive resin composition described in any one of claims 1 to 5 directly or indirectly onto a substrate; a process of irradiating at least a portion of the film with radiation after the process of forming the film; a process of developing the film after the process of irradiating the radiation; and a process of heating the film at a temperature of 60°C or higher and 120°C or lower after the process of developing. Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 delete
Citation Information
Patent Citations
Novel photosensitive resin composition and application thereof
JP2016122153A
Coating solution for forming antireflective coating film comprising polysiloxane modified with mercapto group
KR1020150040374A
Radiation-sensitive composition, insulating film for display device, display device, and process for forming the insulating film
KR1020200129037A
